PENERAPAN MODEL PEMBELAJARAN LANGSUNG BERBANTUAN ALAT PERAGA MESIN FUNGSI UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS XI IPA PADA MATERI KOMPOSISI DUA FUNGSI DI SMAN 3 PALU - Muthia, Sri (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
The aim of this research was to obtain the description of applying the direct learning model aided props machine function in effort to improve students understanding on Â material of composition of the two functions in class XI IPA SMAN 3 Palu. This research is a classroom action research (CAR). As the research design refers to the design of the research of Kemmis and Mc. Taggart that is (1) planning, (2) action, (3) observation and (4) reflection. This research was conducted in two cycles. The research results showed that the applying the direct learning model aided props machine function can increase studentsÂ understanding on material of composition of the two phases following these steps, namely: (1) teacher outlines the objectives and prepare students, (2) teacher presenting and demonstrating of material with aided props machine function, (3) teacher guiding the training with scaffolding techniques, (4) teacher checking students understanding by asking for student to present their answers in front of class and provide feedback, and (5) provide opportunities for advanced training and implementation by providing practice questions alone to students without guided by the teacher.